High-quality infrared imaging with graphene photodetectors at room temperature. Issue 35 (22nd August 2016) - Guo, Nan; Hu, Weida; Jiang, Tao; Gong, Fan; Luo, Wenjin; Qiu, Weicheng; Wang, Peng; Liu, Lu; Wu, Shiwei; Liao, Lei; Chen, Xiaoshuang; Lu, Wei
Abstract : A multispectral active infrared imaging has been demonstrated by using a graphene photodetector based on hybrid response mechanisms at room temperature. Abstract : Graphene, a two-dimensional material, is expected to enable broad-spectrum and high-speed photodetection because of its gapless band structure, ultrafast carrier dynamics and high mobility. We demonstrate a multispectral active infrared imaging by using a graphene photodetector based on hybrid response mechanisms at room temperature. The high-quality images with optical resolutions of 418 nm, 657 nm and 877 nm and close-to-theoretical-limit Michelson contrasts of 0.997, 0.994, and 0.996 have been acquired for 565 nm, 1550 nm, and 1815 nm light imaging measurements by using an unbiased graphene photodetector, respectively. Importantly, by carefully analyzing the results of Raman mapping and numerical simulations for the response process, the formation of hybrid photocurrents in graphene detectors is attributed to the synergistic action of photovoltaic and photo-thermoelectric effects. The initial application to infrared imaging will help promote the development of high performance graphene-based infrared multispectral detectors.